Effect of fibrinogen concentrate administration on early mortality in traumatic hemorrhagic shock: A propensity score analysis. Issue 5 (May 2020) - Hamada, Sophie Rym; Pirracchio, Romain; Beauchesne, Jocelyn; Benlaldj, Mohammed Nadjib; Meaudre, Eric; Leone, Marc; Pottecher, Julien; Abback, Paer Selim; Gauss, Tobias; Boutonnet, Mathieu; Cook, Fabrice; Garrigue, Delphine; et al.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Fibrinogen concentrate is widely used in traumatic hemorrhagic shock despite weak evidence in the literature. The aim of the study was to evaluate the effect of fibrinogen concentrate administration within the first 6 hours on 24-hour all-cause mortality in traumatic hemorrhagic shock using a causal inference approach. METHODS: Observational study from a French multicenter prospective trauma registry was performed. Hemorrhagic shock was defined as transfusion of four or more red blood cell units within the first 6 hours after admission. The confounding variables for the outcome (24-hour all-cause mortality) and treatment allocation (fibrinogen concentrate administration within the first 6 hours) were chosen by a Delphi method. The propensity score was specified with a data-adaptive algorithm and a doubly-robust approach with inverse proportionality of treatment weighting allowed to compute the average treatment effect. Sensitivity analyses were performed. RESULTS: Of 14, 336 patients in the registry during the study period, 1, 027 in hemorrhagic shock were analyzed (758 receiving fibrinogen concentrate within 6 hours and 269 not receiving fibrinogen concentrate). The average treatment effect, expressed as a risk difference, was −0.031 (95% confidence interval, −0.084 to 0.021). All sensitivity analysis confirmed the results. CONCLUSIONS: Fibrinogen concentrate administration within the first 6 hours of a traumatic hemorrhagic shock did not decrease 24-hour all-cause mortality. LEVEL OF EVIDENCE: Prognostic, level III.